Riqueza de aves del Parque Nacional Barranca del Cupatitzio, Michoacán, México - Chávez-León, Gilberto (Instituto de Ecología, A.C., 2007)
Here I report the richness of bird species from Barranca del Cupatitzio National Park, Uruapan, Michoacan, Mexico, recorded monthly from August 2003 to June 2005 by means of specimen collection, visual and aural detection, and photo trapping techniques. I recorded 128 species, belonging to 93 genera, 35 families and 12 orders. The second order Jackknife estimator indicated that 90.8% of all possible species were recorded and at least 13 more species can be potentially found. Out of the 128 species recorded, 93 species are permanent residents, 25 migratory, 4 transient, 5 vagrant and 1 introduced. The endemism included 12% of the species endemic to Mexico and 51.8% of the endemics to the Mexican Transvolcanic Belt. One species is considered as threatened and 6 subject to special protection by Mexican law. Using risk, endemism and distribution criteria, 20 species were identified as priority species for conservation.